Improving preparedness for time critical prehospital care: a descriptive study of the first responder system in Central Norway - Andreas Lindeman; Lars Eide Næss; Lars Vesterhus; Ann-Britt Maude Bakken; Andreas Krüger; Helge Haugland (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background First responders exist in several countries and have been a prehospital emergency medical resource in Norwegian municipalities since 2010. However, the Norwegian system has not yet been studied. The aim of this study was to describe the first responder system in Central Norway and how it is used as a supplement to emergency medical services (EMS). Methods We described incidents with dispatch of first responders in the catchment area of the Emergency Medical Communication Center of Sør-Trøndelag in Central Norway, using retrospective data recorded in the Norwegian Emergency Medical Information System between 2019 and 2023. Results First responders were dispatched to 460 incidents during the period. Of these, 441/460 (96%) incidents were assessed as “acute”, and 135/460 (29%) were assessed as possible cardiac arrests. Four large rural municipalities accounted for 234/460 (51%) of the incidents. One in four patients, 112/449 (25%), died within 30 days. EMS had a median response time of 29 min in our sample. Conclusion First responders are almost exclusively dispatched to high-severity incidents, with suspected cardiac arrest being the most common dispatch criteria. Our findings suggest that the first responder system contributes to rapid response in cases of acute illness and injury, especially in rural areas.